PROSPECTS AND HALLENGESOF MOBILE BANKING IN MAHAD (International Journal of Food and Nutritional Sciences, 2022)
This report presents an in-depth analysis of mobile banking, a rapidly evolving technology that hastransformed the landscape of financial services. The study investigates the impact of mobile banking oncustomer behavior, banking operations, and the overall banking industry. Through a comprehensive reviewof literature, case studies, and empirical research, the report explores the benefits, challenges, and futureprospects of mobile banking